MECHANISM FOR MANAGING INNOVATIVE DEVELOPMENT IN SOCIO-ECONOMIC SYSTEMS: PRINCIPLES AND APPROACHES - Lev I. Ushvitsky; Anna A. Ter-Grigoryants (Вестник Северо-Кавказского федерального университета)
The item presents scientific basics of developing a mechanism for managing innovative development in socio-economic systems of various levels under limited production resources.